Ab-initio study of the ground and low-lying excited states including the spin-orbit effect of RbBa molecule and laser cooling feasibility. (September 2020) - Ladjimi, Hela; Zrafi, Wissem; Allouche, Abdul-Rahman; Berriche, Hamid
Highlights: The PECs of the 16 Λ-S states have been calculated. The PECs of the 33 Ω states arising from spin-orbit coupling of 16 Λ-S states have been studied. Permanent and transition dipole moments and vibrational energy levels have been calculated for all states. Stimulated black body and spontaneous transition rates of vibrational states of the ground state were evaluated. The possibly of direct laser cooling for RbBa molecule have been discussed. Abstract: In this work, we present a thorough theoretical structure and spectroscopic study of the ground and low lying excited states of RbBa molecule. High-level ab-initio calculations are performed, using MCSCF/MRCI+Q level of method, based on the effective core potential (ECP) and core-polarization potential (CPP) approach. The potential energy curves, spectroscopic parameters, vibrationnel energy levels of the 16( 2, 4 Σ +, 2, 4 Π, 2, 4 Δ) first electronic states, with respect to the lowest five dissociation limits were calculated. The comparison of the spectroscopic constants of the ground state X 2 Σ + with the available theoretical work, are in good agreement. The study of all the excited states is performed in this work for the first time. Afterwards, the spin-orbit operator is incorporated in valence MRCI calculation using optimized relativistic spin-orbit pseudo-potentials and 33 Ω states are generated and split into Λ-S states. In addition, both relativistic and non relativistic calculations of permanent and transition dipole moments are presented and discussed. Stimulated black body ( T = 300 K) and spontaneous transition rates of vibrational states of X 2 Σ + state were evaluated. The related vibrational lifetimes for RbBa are found to be in order of 10 3  s which is sufficiently large for ultracold experiments. Moreover, the vibrational life-time for the A 2 Σ + ( v' ) and A 2 П ( v" ) states are measured and the possibility of Laser Cooling for the RbBa molecule is discussed based on Franck–Condon factors calculation of A 2 Σ + ( v' )→ X 2 Σ + ( v ) and A 2 П( v" ) → X 2 Σ + ( v ) transition. This work represents a significant contribution for experimentalists as it provides efficient information in order to form cold alkali and alkaline-earth RbBa molecules.